1998
DOI: 10.1111/j.1574-695x.1998.tb01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble mannan and β-glucan inhibit the uptake ofMalassezia furfurby human monocytic cell line, THP-1

Abstract: The uptake of live and heat-killed Malassezia furfur HIC 3321, HIC 3343 and Candida albicans ATCC 10231 by human monocytic cell line, THP-1, was examined. THP-1 was differentiated by PMA for 7 days before use. The uptake of these yeasts by THP-1 was increased in a concentration-dependent manner of yeasts, and the uptake reached plateau level at the E/T (yeast/THP-1) ratio 5. In addition, a higher percentage of heat-killed cells than live cells was taken in THP-1. Yeast mannan and beta-1,3-glucan, random coiled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although recognition of Malassezia spp. products by TLRs and CLRs has been reported, the possible role of NLRs in innate immune responses to Malassezia spp. had never been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Although recognition of Malassezia spp. products by TLRs and CLRs has been reported, the possible role of NLRs in innate immune responses to Malassezia spp. had never been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…We have long been working on the relationship between the structure and immunomodulating activity of b-glucans, using G. frondosa, [8][9][10] P. vesiculosa, 15) S. sclerotiorum, [11][12][13] S. commune, [21][22][23] O. lapidescens, 14) G. lucidum, 42) S. cerevisiae, 17) C. albicans, 16) M. furfur, 43,44) and S. crispa. 19) During this period, in a preclinical animal study, we found that the activity was significantly dependent on the molecular weight, degree of branching, and conformation.…”
Section: Discussionmentioning
confidence: 99%